PENGARUH CURRENT RATIO DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PT LION METAL WORKS TBK PERIODE 2015-2024 - Anggraini, Reza Deswita; Lisdawati, Lisdawati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the effect of Current Ratio and Earning Per Share on Stock Prices at PT Lion Metal Works Tbk for the 2015-2024 period. The research method used is quantitative research with an associative and descriptive approach where the processed data is secondary data obtained from the financial statements of the company PT Lion Metal Works Tbk using the SPSS 2.5 application. The analysis methods used are descriptive statistical tests, Classical Assumption Tests (Normality, Multicollinearity, Heteroscedasticity and Autocorrelation), Multiple Linear Regression Tests, T Tests, F Tests, Correlation Coefficient Tests, and Determination Coefficient Tests. Based on the results of the study, it shows that the Current Ratio (CR) does not have a significant partial effect on stock prices with a t count of (-0.231 < t table 2.365) with a significance value of (0.824> 0.05). Earning Per Share (EPS) has a partial significant effect on stock prices with a calculated t of (3.936 > ttable 2.365) with a significance value of (0.0006 < 0.05). Current Ratio (CR) and Earning Per Share (EPS) have a simultaneous significant effect on stock prices with an calculated F of (8.708 > Ftable 4.74) with a significance value of (0.013 < 0.05).